2022
DOI: 10.3390/vaccines10050780
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing COVID-19 Vaccine Uptake among Nepali People in the UK: A Qualitative Study

Abstract: Vaccination saves lives and can be an effective strategy for preventing the spread of the COVID-19, but negative attitudes towards vaccines lead to vaccine hesitancy. This study aimed to explore the factors influencing the uptake of the COVID-19 vaccine in the Nepali community in the United Kingdom (UK). This qualitative study included in-depth interviews with 20 people from Nepal living in the UK. Interviews were conducted by a native-Nepali speaker and all interviews were audio-recorded, transcribed, and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
(57 reference statements)
1
10
0
Order By: Relevance
“…These reasons corresponded to the findings of other studies which explored vaccine acceptance, although the influence of others was more pronounced and there was more ambivalence about the vaccines' safety and effectiveness. [4][5][6] In our previous study we found that exposure to COVID-19 misinformation had led to confusion, distress and mistrust and was contributing to uncertainty in vaccine intentions. Our follow up study found that the majority of participants and those close to them had managed to overcome the tidal wave of misinformation and get the vaccine.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These reasons corresponded to the findings of other studies which explored vaccine acceptance, although the influence of others was more pronounced and there was more ambivalence about the vaccines' safety and effectiveness. [4][5][6] In our previous study we found that exposure to COVID-19 misinformation had led to confusion, distress and mistrust and was contributing to uncertainty in vaccine intentions. Our follow up study found that the majority of participants and those close to them had managed to overcome the tidal wave of misinformation and get the vaccine.…”
Section: Discussionmentioning
confidence: 96%
“…These reasons corresponded to the findings of other studies which explored vaccine acceptance, although the influence of others was more pronounced and there was more ambivalence about the vaccines’ safety and effectiveness. 4-6…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies focused on COVID‐19 vaccine acceptance found that people were motivated by wanting to protect themselves and others, by trust in science and the evidence of vaccines' effectiveness, by trust in their GP and by wanting to get back to normal life after periods of social restrictions. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%